Influence of the camber trailing-edge wings on the motion performance of underwater gliders - Yuhong Liu; Shixun Xu; Shan Tian; Shiquan Lan; Shihan Deng; Shuhe Liu; Dengxue Feng (International Journal of Naval Architecture and Ocean Engineering, 2022)
Wings are the main source of lift for Underwater Gliders (UGs) and play a decisive role in their motion performance. The wings of UGs are generally rectangular and symmetrical airfoils. In this study, a mini-UG with flexible camber trailing-edge wings was proposed and developed to investigate the influence of the trailing edge of the wings on the motion performance of UGs. Flexible deformation of the trailing edge was realized using a steer-by-wire actuator. The test results showed that the trailing edge of the wing could realize maximum upward/downward sloping angles of +16°/−16°. By combining computational fluid dynamics simulations and tank experiments, this study obtained the glide efficiency (in lift-drag ratio) and stable margins of a mini-UG with variable camber trailing-edge wings. The results showed that the angles of attack corresponding to the minimum lift-to-drag ratio were all negative in cases of downward sloping and positive in cases of upward sloping. Moreover, the suitable camber of the trailing edge, that is, downward-sloping trailing edge on descending glides and upward-sloping trailing edge on ascending glides, can not only greatly improve glide efficiency but also benefit flight stability. Tank experiments showed that the lift-to-drag ratio of the mini-UG with appropriate variable camber trailing-edge wings can be increased by at least 25% compared to those with a symmetrical airfoil.